Brain dystrophin-glycoprotein complex: Persistent expression of beta-dystroglycan, impaired oligomerization of Dp71 and up-regulation of utrophins in animal models of muscular dystrophy - Culligan, Kevin (BioMed Central, 2001)
BACKGROUND: Aside from muscle, brain is also a major expression site for dystrophin, the protein whose abnormal expression is responsible for Duchenne muscular dystrophy. Cognitive impairments are frequently associated with this genetic disease, we therefore studied the fate of brain and skeletal muscle dystrophins and dystroglycans in dystrophic animal models. RESULTS: All dystrophin-associated glycoproteins investigated were reduced in dystrophic muscle fibres. In Dp427-deficient mdx brain and Dp71-deficient mdx-3cv brain, the expression of α-dystroglycan and laminin was reduced, utrophin isoforms were up-regulated and β-dystroglycan was not affected. Immunofluorescence localization of β-dystroglycan in comparison with glial, endothelial and neuronal cell markers revealed co-localization of von Willebrand factor with β-dystroglycan. Its expression at the endothelial-glial interface was preserved in dystrophin isoform-deficient brain from mdx and mdx-3cv mice. In addition, chemical crosslinking revealed that the Dp71 isoform exists in mdx brain predominantly as a monomer. CONCLUSIONS: This suggests an association of β-dystroglycan with membranes at the vascular-glial interface in the forebrain. In contrast to dystrophic skeletal muscle fibres, dystrophin deficiency does not trigger a reduction of all dystroglycans in the brain, and utrophins may partially compensate for the lack of brain dystrophins. Abnormal oligomerization of the dystrophin isoform Dp71 might be involved in the pathophysiological mechanisms underlying abnormal brain functions.